Virtual System for Industrial Processes: Distillation Towers - Jácome, Efren (2021)
In this paper a realistic and intuitive virtual environment of a distillation tower system is developed. The three-dimensional model of the system is based on a real system, which is replicated in Blender software to be later implemented in Unity, in order to simulate its behavior. By showing the evolution of the system, control and monitoring maneuvers are implemented, so that the virtual animation is similar to a real process. The application developed is intended to provide support in the learning process of an operator in the work area